Tłumienie Falami Naprężeń w Belkach Sprężystych - Więckowski, J. (Engineering Transactions, 1958)
An analogy is indicated between vibrations in elastic bodies and in liquids. In a number of cases of forced vibration of infinite elastic beams, reaction forces of these beams are found. It is pointed out that for a series of cases of harmonic or exponential vibrations, these forces have the form of viscous friction forces with the coefficient of damping depending on the frequency and the constants characterizing the elastic properties and the geometry of the beam. For a certain simple case of forced vibration, the reduced mass of an infinite beam is determined in function of the above constants. The results obtained are illustrated by simple examples of vibration of a harmonic oscillator connected with an infinite elastic beam.